Hepatic neuroendocrine neoplasm: imaging patterns - Houat,Abdallah de Paula (2020)
Neuroendocrine neoplasms (NENs) are a heterogeneous group of tumors with distinct morphological and biological manifestations, the liver being the main organ affected by its metastases. However, primary hepatic involvement is quite rare. Hepatic NENs can have a variety of radiological presentation forms and can therefore mimic other lesions, making their diagnosis challenging. Nonetheless, certain imaging aspects allow NENs to be included among the main differential diagnoses of hepatic lesions and can guide the search for an extrahepatic primary site when the probable diagnosis is metastases.